A retrospective analysis of computed tomography findings in patients with pulmonary complications after allogeneic hematopoietic stem cell transplantation. Issue 12 (December 2015) - Ugai, Tomotaka; Hamamoto, Kohei; Kimura, Shun-ichi; Akahoshi, Yu; Nakano, Hirofumi; Harada, Naonori; Kameda, Kazuaki; Wada, Hidenori; Yamasaki, Ryoko; Ishihara, Yuko; Kawamura, Koji; Sakamoto, Kana; et al.
Abstract: Objective: The purpose of this study was to review the high-resolution computed tomography (CT) findings in patients with pulmonary complications after allogeneic hematopoietic stem cell transplantation (HSCT), and to evaluate the relationship between CT findings and clinical outcomes. Patients and methods: We collected the clinical data in 96 consecutive patients who underwent CT scan for pulmonary complications after allogeneic HSCT and analyzed the relationships among these clinical characteristics, CT findings and clinical responses. Radiologists who were blinded to clinical information evaluated the CT findings. Results: In multivariate analyses, the presence of chronic graft-versus-host disease (GVHD) and non-segmental multiple consolidations were significantly associated with a poor response to antimicrobial therapies, and the disease risk was significantly associated with a poor corticosteroid response. In addition, the existence of cavity formation and pleural effusion were significantly associated with a fatal prognosis. Twenty-five patients underwent bronchoscopic examination and 4 of them also underwent transbronchial lung biopsy (TBLB), but diagnostic information was not obtained in 15 patients. There was no significant association between specific CT findings and the diagnosis based on bronchoscopic examination. Conclusions: No specific CT finding was identified as a predictor for either an antimicrobial response or for a corticosteroid response in this study. The presence of cavity formation and pleural effusion may predict a poor prognosis.